Single-Cell Transcriptomic Analysis Reveals the Crosstalk Propensity Between the Tumor Intermediate State and the CD8+ T Exhausted State to be Associated with Clinical Benefits in Melanoma - Zhu, Jiali; Yan, Min; Yan, Haoteng; Xu, Liwen; Jiang, Zedong; Liao, Gaoming; Zhou, Yao; Liu, Wei; Liang, Xin; Li, Xia; Xiao, Yun; Zhang, Yunpeng (Frontiers in Immunology, 2022)
Heterogeneous crosstalk between tumor cells and CD8+ T cells leads to substantial variation in clinical benefits from immunotherapy in melanoma. Due to spatial distribution and functional state heterogeneity, it is still unknown whether there is a crosstalk propensity between tumor cells and CD8+ T cells in melanoma, and how this crosstalk propensity affects the clinical outcome of patients. Using public single-cell transcriptome data, extensive heterogeneous functional states and ligand–receptor interactions of tumor cells and CD8+ T cells were revealed in melanoma. Furthermore, based on the association between cell–cell communication intensity and cell state activity in a single cell, we identified a crosstalk propensity between the tumor intermediate state and the CD8+ T exhausted state. This crosstalk propensity was further verified by pseudo-spatial proximity, spatial co-location, and the intra/intercellular signal transduction network. At the sample level, the tumor intermediate state and the CD8+ T exhausted state synergistically indicated better prognosis and both reduced in immunotherapy-resistant samples. The risk groups defined based on these two cell states could comprehensively reflect tumor genomic mutations and anti-tumor immunity information. The low-risk group had a higher BRAF mutation fraction as well as stronger antitumor immune response. Our findings highlighted the crosstalk propensity between the tumor intermediate state and the CD8+ T exhausted state, which may serve as a reference to guide the development of diagnostic biomarkers for risk stratification and therapeutic targets for new therapeutic strategies.